The association between parents phubbing and prosocial behavior among Chinese preschool children: a moderated mediation model - Shi, Dasheng; Xu, Yongqi; Chu, Lin (Frontiers in Psychology, 2024)
In China, the popularization and widespread use of smartphones and other electronic devices have led to the occurrence of "parents phubbing", which may have a negative impact on child-parent relationship and preschoolers' prosocial behavior.To clarify this process, this study examined the relationship between between parents phubbing, closeness child-parent relationship, authoritative parenting style and children's prosocial behavior. A questionnaire survey was conducted with 3,834 parents from 20 kindergartens in Zhuhai, China. According to the study, we found a significant negative correlation between parents phubbing and preschoolers' prosocial behavior. Closeness child-parent relationship mediated between parents phubbing and preschoolers' prosocial behavior through mediation effects analysis. In other words, parent phubbing was negatively associated with closeness child-parent relationship, which in turn predicted less child prosocial behavior. In addition, authoritative parenting styles have a moderating effect. As the level of authoritative parenting style increases, the negative impact of parent phubbing on the prosocial behavior of preschool children is attenuated. This study contributes to the understanding of the relationship between parents phubbing and prosocial behaviors of preschool children, as well as the internal mechanisms at work. Practically, the study suggests that parents should reduce the incidence of phubbing in their contact with their children and, at the same time, work to improve the child-parent relationship and promote the development of prosocial behaviors in children.